Book Review: The Anthropocene as a geological time unit: a guide to the scientific evidence and current debate, by J. Zalasiewicz, C.N. Waters, M. Williams & C.P. Summerhayes, 2019. Cambridge University Press, Cambridge, UK. 361 pages. Hardback: price £44.99, ISBN 9781108475235. - Tylmann, Wojciech (Geologos, 2021)
Book Review: The Anthropocene as a geological time unit: a guide to the scientific evidence and current debate, by J. Zalasiewicz, C.N. Waters, M. Williams & C.P. Summerhayes, 2019. Cambridge University Press, Cambridge, UK. 361 pages. Hardback: price £44.99, ISBN 9781108475235.